Pertosylated pillar[5]arene: Self-template assisted synthesis and supramolecular polymer formation - Araya Ruengsuk (2020)
© The Royal Society of Chemistry. A facile synthesis of decatosylate pillar[5]arene 1 is reported in excellent yield (>70%). The high yield is attributed to a self-template effect of the pendant tosylate arms. The X-ray crystal structure shows the formation of a linear supramolecular polymer, stabilised by intermolecular pillar[5]arene-tosylate inclusion complexes. These polymeric arrays persist in solution and form rod-like microfibril nanostructures evidenced by SEM. This journal is